PREVALENCE AND IDENTIFICATION OF ECTOPARASITES LICE IN DOMESTIC CHICKEN IN BALI - Gusti Ayu Putu Ratih Puspasari; Ida Bagus Made Oka; I Made Dwinata (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Free-range chicken is Indonesia's natural wealth which has various benefits as laying poultry, broilers and religious ceremonies. One of the ectoparasites that attack free-range chickens in Bali is lice. This study was conducted to determine the prevalence of free-range chicken lice in Bali and identify the type of lice in free-range chickens in Bali. So that precise control can be carried out. Lice were obtained from 60 free-range chickens in several areas of Bali, namely Tabanan, Badung, and Gianyar regencies. Sampling is done by combing chicken feathers using cotton swabs slightly moistened with 70% alhokol. The ticks collected come from several regions on the chicken's body, namely the head-neck, back, chest, and wings. The obtained lice are then inserted into an affendorf tube that has contained 70% alcohol and labeled to distinguish one chicken from another. Then the identification process is carried out. The results showed that the prevalence of lice infestation in free-range chickens in Bali was 53% with Tabanan (50%), Badung (25%) and Gianyar (85%) regencies. The types of ticks found are Menopon gallinae, Lipeurus caponis, Gonoicotes gallinae, and Menacanthus straminaeus.